Spinal Cord Stimulation Control Modalities: Open-loop versus Closed-loop and Perspectives - Zheng, Zhide; Cai, Jiacheng (Transactions on Computer Science and Intelligent Systems Research, 2024)
Spinal cord stimulation is currently widely used in the treatment of chronic pain, which has a prominent effect on reducing pain in the trunk and limbs. With the development of related technology, spinal cord stimulation has shown great advantages in the field of pain management and a lot of stimulation methods have been born. This paper will first introduce the working principle of spinal cord stimulation and introduce several typical open-loop stimulation methods, including conventional tonic SCS, High Frequency SCS and Burst SCS. Then it will analyze the factors that affect the stimulation effect. The concept of electrically evoked compound action potentials (ECAPs) is explained, and then the closed-loop SCS controlled by ECAPs are introduced and their working principle is explained. Finally, the future development direction of this field is prospected, and it is believed that this field needs a convincing quantitative index. Finally, the possible development direction of technology is given.